Prototipe Perangkat untuk Pemantauan dan Pengendalian Berbasis Web Diiintegrasikan ke Smarthome System - Achmad Faris Nasyarudin; Ritzkal Ritzkal; Arief Goeritno (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
The design and construction of a device prototype for a water level measurement system in a tank and controlling a number of garden light analogies has been carried-out and the prototype can be integrated into smarthome system. Three topics are discussed in this paper, including the manufacture, programming, and performance measurement of device prototypes. The formation of prototype of the device is done through wiring integration between electronic devices, in order to obtain the hardware handshacking. Programming the prototype of device is done through the creation of algorithms and preparation of syntax, in order to obtain the software handshacking. The performance of the prototype of device is measured when integrated into the Smarthome system, in order to obtain the hardware and software handshacking. The performance of prototype of the device when monitoring in the form of information about the water level in the water tank with 3 (three) conditions, namely the criteria of